Legal Framework on the Marine Environment Protection of Straits used for International Navigation: Has It Been Effective in the Straits of Malacca and Singapore? - Rusli, H; Dremliuga, R; Talaat, WI (Yijun Inst Int Law, 2024)
Indexed by WOS/ Scopus